Strengthening the protection of financial consumers in Mongolia banking sector. - Giannetto, Giacomo ([Manila] Asian Development Bank, 2019)
The assessment includes recommendations for Mongolian policy makers on ways to improve the regulatory framework and the supervisory oversight of financial consumer protection and the role that the Bank of Mongolia could play. The analyses focuses on the banking industry in Mongolia, which currently accounts for over 90% of the entire financial services industry. However, a significant number of the proposed recommendations may be equally applicable to other financial markets, such as insurance and investment and securities services, and several unregulated services.
Keywords: Financial institutions -- Mongolia; Banks and banking -- Mongolia; Electronic books